JENIS DAN KEPADATAN TUNGAU DEBU RUMAH YANG DITEMUKAN DI KELURAHAN TELING BAWAH KECAMATAN WENANG KOTA MANADO - Kawulur, Yohanes C. W.; Tuda, Josef S. B.; Wahongan, Greta J. P. (Universitas Sam Ratulangi, 2013)
Abstract: Based on data from district Wenang health centers, there are many known cases of asthma and dermatitis. Asthma and dermatitis can be caused by the presence of dust mites. House dust mites are found in damp houses, mattresses, pillows, bolsters, carpets and many other home furnishings. It highest population was found in the bedroom of dust, especially in mattress dust.. The purpose of this study to determine the species and density of house dust mites in the Teling Bawah Village, District of Wenang Manado City. This research method is descriptive survey with a cross-sectional approach (cross-sectional). Samples were collected from people's homes in the Teling Bawah Village, District of Wenang Manado City then examined in the laboratory of Parasitology, Faculty of Medicine, University of Sam Ratulangi Manado. Results of this study found four species of house dust mites are Dermatophagoides spp, acarus spp, Glycyphagus destrucor spp, and Tarsonemus spp. House dust mite densities obtained an average of 2.21 in the bedroom and 2.13 in the living room. Conclusion: TDR type most commonly found are Dermatophagoides spp and TDR density in the bedroom is higher than in the living room.Keywords: house dust mites, species, densityAbstrak: Berdasarkan data dari puskesmas Kecamatan Wenang, diketahui banyak terdapat kasus asma dan dermatitis. Asma dan dermatitis bisa diakibatkan oleh keberadaan tungau debu rumah. Tungau debu rumah banyak ditemukan pada rumah yang lembab, kasur, bantal, guling, karpet serta berbagai perabot rumah yang lain. Populasi TDR terbanyak didapatkan pada debu kamar tidur terutama pada debu kasur. Tujuan penelitian ini untuk mengetahui jenis dan kepadatan tungau debu rumah di Kelurahan Teling Bawah Kecamatan Wenang Kota Manado. Metode penelitian ini secara survey deskriptif dengan pendekatan potong lintang (cross sectional). Sampel penelitian dikumpulkan dari rumah-rumah penduduk di Kelurahan Teling Bawah Kecamatan Wenang Kota Manado kemudian diteliti di laboratorium Parasitologi Fakultas Kedokteran, Universitas Sam Ratulangi Manado. Hasil penelitian ini ditemukan 4 jenis tungau debu rumah yaitu Dermatophagoides spp, Acarus spp, Glycyphagus destrucor spp, dan Tarsonemus spp. Kepadatan tungau debu rumah didapatkan rata-rata 2,21 di kamar tidur dan 2,13 di ruang tamu. Simpulan: Jenis TDR yang paling banyak ditemukan yaitu Dermatophagoides spp serta kepadatan TDR di kamar tidur lebih tinggi dibandingkan di ruang tamu.Kata kunci: Tungau debu rumah, jenis, kepadatan